FGF Gradient Controls Boundary Position Between Proliferating and Differentiating Cells and Regulates Lacrimal Gland Growth Dynamics - Thotakura, Suharika; Basova, Liana; Makarenkova, Helen P. (Frontiers in Genetics, 2019)
Fibroblast Growth Factor (FGF) signaling plays an important role in controlling cell proliferation, survival and cell movements during branching morphogenesis of many organs. In mammals branching morphogenesis is primarily regulated by members of the Fgf7-subfamily (FGF7 and FGF10), which are expressed in the mesenchyme and signal to the epithelial cells through the “b” isoform of fibroblast growth factor receptor-2 (Fgfr2). Our previous work demonstrated that Fgf7 and FGF10 form different gradients in the extracellular matrix and induce distinct cellular responses and gene expression profiles in the lacrimal and submandibular glands. The last finding was the most surprising since both FGF7 and FGF10 bind signal most strongly through the same fibroblast growth factor receptor-2b isoform (FGFR2b). Here we revisit this question to gain an explanation of how the different FGFs regulate gene expression. For this purposes we employed our ex vivo epithelial explant migration assay in which isolated epithelial explants are grown near the Fgf loaded beads. We demonstrate that the graded distribution of Fgfs induce activation of ERK1/2 MAP kinases that define the position of the boundaries between proliferating and differentiating cells and gene expression profiles of the epithelial explants strictly depends on the ratio between ‘bud’ and ‘stalk’ area. Our data also suggests that differentiation of ‘stalk’ and ‘bud’ regions within the epithelial explants is necessary for directional and persistent explant migration. Gaining a better understanding of FGF functions is important for development of new approaches to enhance tissue regeneration.